Introduction: The end of a parable? Unsettling the transitology model in the age of crisis - Kornetis, Kostis (Historein, 2015)
This volume brings together scholars from the fields of history, political science, political economy, historical sociology and cultural studies, to comment on the theoretical and empirical unsettling of democratic transitions at the time of the economic crisis. The volume links together transitions in time and space, reappraising the democratic processes in Southern Europe in the mid-1970s, the post-1989 transformations in Eastern Europe, the effects of Southern Cone democratisations and the 2011 revolts in the Arab worlds, resisting both temporal particularities and national exceptionalisms. It further showcases how even supposed model transitions came under attack during the current economic crisis, thus highlighting the incloncusive nature of these events and the strong interconnections between past and present.